PENGAMATAN EPIDERMIS DAUN MENGGUNAKAN METODE PRINTING DAN IRISAN PARADERMAL - Hesti Kurniahu (Prodi Biologi Universitas PGRI Ronggolawe, 2023)
Observation of leaves, especially the epidermis, is often the focus of research because this part is directly exposed to the environment, so changes that occur in this part can indicate changes in the plant's metabolism. Observation of leaf skin requires preparation in advance, especially in observing wet preparations. There are various methods of leaf skin sample preparation including the printing method and leaf paradermal slices. The purpose of this study was to compare leaf preparations with preparations using the printing method and paradermal slices carried out by students of the Biology at PGRI Ronggolawe University in the Plant Anatomy Practicum course. Data in the form of preparations of leaves Morinda citrifolia and Solanum melongen were observed using an electric microscope with a magnification of 400 times, while Ixora sp. leaves were observed using a light microscope with a magnification of 400 times. The results of the study can be concluded that the printing and paradermal incision methods are optimal for the purpose of observing different leaf characters. The optimal printing method is used on leaves that have little or no trichomes and is very good for observing stomatal openings. While the paradermal slice method is good for use on leaves that have trichomes or not, the use of this method requires good practical skills, besides this method cannot represent leaf stomatal openings at the time of observation because the stomata tend to close.